1972
DOI: 10.1063/1.1678761
|View full text |Cite
|
Sign up to set email alerts
|

ESR Identification of Slater Configurations and of Exchange of the (AsO4)4− Radical in Irradiated Ferroelectric KH2AsO4 and KD2AsO4 and Antiferroelectric NH4H2AsO4 and ND4D2AsO4

Abstract: The ESR study of the g̃ spectroscopic tensor and the As hyperfine tensor T̃As of the (AsO4)4− radical in crystals of ferroelectric KDA and DKDA and antiferroelectric ADA and DADA shows that it is possible to identify selectively the Slater configurations of the radical in these crystals. In the paraelectric phase of these crystals we observe dynamic low frequency fluctuations of g̃ and T̃As which correspond to an exchange between the ``upper'' and ``lower'' Slater configurations of the radical. The temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

1973
1973
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(12 citation statements)
references
References 23 publications
0
9
0
3
Order By: Relevance
“…From physical point of view, this means the following phase transition mechanisms at negativeε: a significant tunnelling destroys the ground state ferroelectric configuration created by the short range interactions, whereas the long range interactions establish an antiferroelectric ordering. However, the existence of this mechanisms can be verified only with new experimental studies; in particular, the results of [45] should be confirmed. Therefore, at present it is difficult to unambiguously choose between the sets 2 and 3 for NH 4 H 2 AsO 4 .…”
Section: Numerical Analysis and Comparison With Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…From physical point of view, this means the following phase transition mechanisms at negativeε: a significant tunnelling destroys the ground state ferroelectric configuration created by the short range interactions, whereas the long range interactions establish an antiferroelectric ordering. However, the existence of this mechanisms can be verified only with new experimental studies; in particular, the results of [45] should be confirmed. Therefore, at present it is difficult to unambiguously choose between the sets 2 and 3 for NH 4 H 2 AsO 4 .…”
Section: Numerical Analysis and Comparison With Experimental Datamentioning
confidence: 99%
“…In [45] using the EPR it was established that in the disordered phase of the NH 4 H 2 AsO 4 crystal the number of up-down configurations of the H 2 AsO 4 radicals is larger than that of the lateral configurations. It means that the configurational energyε in NH 4 H 2 AsO 4 can be negative.…”
Section: Numerical Analysis and Comparison With Experimental Datamentioning
confidence: 99%
“…A need to revisit the developed theory of the phase transitions in antiferroelectric orthophosphates was indicated by the results of EPR studies. [55]. They showed that in the disordered phase in NH 4 H 2 AsO 4 there exist more upper/lower configurations of H 2 AsO 4 groups than lateral ones.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the phosphate groups in NHaH2PO 4 and KHzPO 4 are POz(OH)2 groups. The PO3(OH ) and PO(OH)3 groups discussed by Takagi (1948) are transient excited states representing a small part of the population of phosphate groups in ADP or KDP (see the work on RT-NH4HzAsO4 by Lamotte, Gaillard & Constantinescu, 1972). The geometrical shape of ordered POz(OH)2 groups is known from several precise crystal structure determinations" ferroelectric KH2PO 4 (Bacon & Pease, 1955), N2H6(H2PO4) 2 (Liminga, 1966) and NzHs(HzPO4) (Liminga, 1965).…”
Section: Disorder In Room-temperature Adp and Kdpmentioning
confidence: 99%